Relationship lending in the interbank market and the price of liquidity - Falk Bräuning; Falko Fecht (Deutsche Bundesbank, 2012)
This paper empirically investigates the effect of interbank relationship lending on banks' access to liquidity. Our analysis is based on German interbank payment data which we use to create a panel of unsecured overnight loans between 1079 distinct borrower-lender pairs. The data shows that banks rely on repeated interactions with the same counterparties to trade liquidity. For the price of liquidity, we find that in the run-up to the recent financial crisis of 2007/08 relationship lenders charged already higher interest rates to their borrowers after controlling for other bank specific characteristics and general market conditions. By contrast, during the crisis borrowers paid on average lower rates to their relationship lenders compared to spot lenders. The observed interest rate differences are statistically and economically significant and in line with theory that relationship lenders have private information about the creditworthiness of their close borrowers.
Keywords: D61; E44; G10; G21; 330; Interbank Market; Relationship Lending; Liquidity Crisis; Central Counterpart; Financial Contagion